Autoimmune Cytopenias In Common Variable Immunodeficiency - Abraham, Roshini S.; Podjasek, Jenna C. (Frontiers in Immunology, 2012)
Common variable immunodeficiency (CVID) is a humoral immunodeficiency whose primary diagnostic features include hypogammaglobulinemia involving two or more immunoglobulin isotypes and impaired functional antibody responses in the majority of patients. While increased susceptibility to respiratory and other infections is a common thread that binds a large cross-section of CVID patients, the presence of autoimmune complications in this immunologically and clinically heterogeneous disorder is recognized in up to two-thirds of patients. Among the autoimmune manifestations reported in CVID (20-50%)(Chapel et al., 2008;Cunningham-Rundles, 2008), autoimmune cytopenias are by far the most common occurring variably in 4-20% (Michel et al., 2004;Chapel et al., 2008) of these patients who have some form of autoimmunity. Association of autoimmune cytopenias with granulomatous disease and splenomegaly has been reported. The spectrum of autoimmune cytopenias includes thrombocytopenia, anemia and neutropenia. While it may seem paradoxical “prima facie” that autoimmunity is present in patients with primary immune deficiencies, in reality, it could be considered two sides of the same coin, each reflecting a different but inter-connected facet of immune dysregulation. The expansion of CD21low B cells in CVID patients with autoimmune cytopenias and other autoimmune features has also been previously reported. It has been demonstrated that this unique subset of B cells is enriched for autoreactive germline antibodies. Further, a correlation has been observed between various B cell subsets, such as class-switched memory B cells and plasmablasts, and autoimmunity in CVID. This review attempts to explore the most recent concepts and highlights, along with treatment of autoimmune hematological manifestations of CVID.